Predicting Interval of Product Reliability With Bootsrap Percentile Method - Akhmad Fauzy; Epha Diana Supandi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
In this article, two methods are proposed to give the interval estimation for reliability function from a product. Reliability function is a probability of an individual (product) surviving till time t. Some resecearchers usually use traditional method to construct interval estimation. This interval needs an assumption that sample is exponentially distributed. This research applied another method, namely Bootstrap percentile. Bootstrap method is more potential in constructing interval estimation for reliability function from a product.